2010
DOI: 10.1098/rsta.2010.0092
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific models of human trachea to predict mechanical consequences of endoprosthesis implantation

Abstract: Nowadays, interventions associated with the implantation of tracheal prostheses in patients with airway pathologies are very common. This surgery may promote problems such as migration of the prosthesis, development of granulation tissue at the edges of the stent with overgrowth of the tracheal lumen or accumulation of secretions inside the prosthesis. Among the movements that the trachea carries out, swallowing seems to have harmful consequences for the tracheal tissues surrounding the prosthesis. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Previous simulations made on physiological swallowing and with real-patient-tracheal geometries and swallowing trajectories showed that almost the same axial force, with an average of 13.5 N, is necessary to close the glottis during the swallowing movement (Perez del Palomar et al 2010;Trabelsi et al 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous simulations made on physiological swallowing and with real-patient-tracheal geometries and swallowing trajectories showed that almost the same axial force, with an average of 13.5 N, is necessary to close the glottis during the swallowing movement (Perez del Palomar et al 2010;Trabelsi et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…These are normally focused on quantifying particles deposition for aerosol techniques Balashazy et al 1996;Nowak et al 2003), on the development of analytical models simulating an isolated tracheal ring (Holzhäuser and Lambert 2001), on analyzing the mechanism of mucosal folding that explains the difference in airway narrowing between asthmatic and control airways (Wiggs et al 1997), or on tracheal finite element models used to predict the behavior of animal (Costantino et al 2004) or human trachea (Gustin et al 1996;Perez del Palomar et al 2010;Trabelsi et al 2011Trabelsi et al , 2014Perez del Palomar et al 2010) with and without an inserted prosthesis. While some studies use structural simulations on real human geometries (Perez del Palomar et al 2010;Trabelsi et al 2011Trabelsi et al , 2012Trabelsi et al , 2014 other studies solve the computational fluid dynamics (CFD) problem applied to approximate (Calay et al 2002;Nowak et al 2003;Ma and Lutchen 2006) or real (Tawahai et al 2004;Gemci et al 2008;Luo and Liu 2008;Wall et al 2010) tracheal geometries. Only few studies have been recently oriented to the coupling between fluid and solid.…”
Section: Introductionmentioning
confidence: 99%
“…17, No. 7, 750-767, http://dx.doi.org/10.1080/10255842.2012.715639 (Malvè et al 2010(Malvè et al , 2011Perez del Palomar et al 2010;Trabelsi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in previous studies [23][24][25], we presented numerical analyses of the tracheal stenting technique proposing possible preoperative planning software designed to support thoracic surgical decisions. Recently we also analyze the tracheal behavior under implantations of different stent type (Dumon© and Ultraflex© stent) [21] with the aim of studying the impact of different prostheses on the smooth muscle and evaluate the risk of stent migration.…”
Section: Introductionmentioning
confidence: 99%